Pengaruh Kepercayaan, Keamanan dan User Experience terhadap Niat Penggunaan dan User Satisfaction: Studi Kasus pada Aplikasi Bank Digital SeaBank - Ramadhan, R. Audi Cahya Lucky; Dhani, Nova Rahma; Devi, Lauro Sitho; Susilowati, Talabiah (TEKNOBIS : Jurnal Teknologi, Bisnis dan Pendidikan, 2026)
This study aims to evaluate the influence of trust, perceived security and user experience on user intention to use and user satisfaction of the SeaBank digital banking application. The method used in this study is quantitative with a survey approach involving 154 respondents, which were analyzed using Structural Equation Modeling–Partial Least Square (SEM–PLS). The results of the analysis show that security does not have a significant impact on intention to use, but has a positive and significant impact on user satisfaction. Trust is proven to contribute positively and significantly to intention to use and user satisfaction. In addition, user experience also has a positive and significant influence on intention to use and user satisfaction. On the other hand, intention to use does not show a significant impact on user experience. This research is expected to provide material for development from the technical and business sides in increasing the number of Seabank application users.